Implementasi Metode Clarke and Wright Savings dalam Penyelesaian Vehicle Routing Problem di PT. Adiguna Gasindo - Munir, Misbahul; Kurniawan, Muchamad; M, Moch. Kalam; Setyawati, Indah (LPPM STT Terpadu Nurul Fikri, 2023)
A vehicle routing problem (VRP) is a problem in finding the most optimal route with the addition of a constraint. PT. Adiguna Gasindo is one of the LPG gas agents who needs help in shipping to agents, the problem is that there is a limit to the amount of LPG cargo that can be transported. In this research, we will solve the LPG delivery problem by optimizing distance and cost. The Clarke and Wright Savings Method, commonly known as the Saving Matrix, will be implemented to complete VRP. In this study, the distance approaches are the nearest insert and nearest neighbor. The test scenarios were carried out using three types of vehicles with different capacities, namely small (225 kg), medium (275 kg), and large (480 kg). The results obtained will be compared with the actual results (routes done) due to validation. From the results of 90 different scenarios, the results obtained by vehicles with large loads are those of vehicles that get the most optimal route in terms of distance and cost. The saving matrix will be more optimal if it is done by adding the nearest insert or nearest neighbor technique.